Active sites provided by the surface autocatalytic effect and quantum confinement for stable and efficient photocatalytic hydrogen generation. Issue 26 (22nd June 2021) - Jia, Ruiming; Gui, Qingfeng; Sui, Lina; Huang, Yan; Lu, Honggang; Dong, Hongzhou; Ma, Shuai; Gan, Zhixing; Dong, Lifeng; Yu, Liyan
Abstract : A metal-free photocatalyst is constructed by anchoring the ultrasmall SiC NCs on carbon nitride nanosheets for efficient and durable hydrogen generation. Abstract : Photocatalytic hydrogen evolution from water is a promising approach for renewable energy generation and storage. However, traditional photocatalysts suffer from limited hydrogen evolution rates due to the lack of active sites. In this work, we demonstrate that a plenty of active sites can be provided by the surface autocatalytic effect and quantum confinement of ultrasmall SiC nanocrystals (NCs). A metal-free photocatalyst is constructed by anchoring the ultrasmall SiC NCs on carbon nitride (CN) nanosheets for efficient and durable hydrogen generation. Moreover, the optical absorption in the visible range and the separation of electrons and holes are significantly improved by the heterojunction band alignment. As a consequence, the CN/SiC NC composite exhibits a high hydrogen evolution rate up to 1889 μmol g −1 h −1 under visible light irradiation with an apparent quantum yield (AQY) of 9.8% at 420 nm. And the photocatalyst shows high stability in the cyclic test. This work provides a new strategy to develop highly efficient photocatalysts for hydrogen generation via the surface autocatalytic effect and quantum confinement.